Social and Legal Prerequisites for Protecting the Property Interests of the Suspect and the Accused in the Application of Coercive Measures - T. T. Bayazitov (Сибирское юридическое обозрение, 2023)
The modern development of social relations cannot be considered in isolation from the economic basis of human life. Taking into account the consistent formation of the institution of private property and the property sphere, new rules for the relationship between the state and the individual are being formed. On this background, issues related to the implementation of the repressive function of the state are of great importance. The process of investigating criminal activity often affects the property interests of the participants in the criminal process. At the same time, the rules of this type of state activity enshrined in the legislation do not always take into account the changed format of economic relations between individuals and legal entities. The article deals with the problem of the lack of adaptation of the criminal procedural legislation to the actual relations in the area of public life. Questions of interaction between criminal procedure and civil legislation are described here. There is a lack of an integrated approach to regulating the issues of protecting the property interests of the suspect, the accused in the application of measures of procedural coercion. Despite the general approach in this area of relations formulated in the Constitution of the Russian Federation, which is favorable for the suspect and for the accused, there are multiple contradictions at the level of intersectoral regulation. The paper states the need for a comprehensive regulation of the features of the application of coercive measures of a property nature to the specified participants in the criminal process. Judicial practice contributes to this process. The decisions of the Constitutional Court of the Russian Federation studied in the article forces the legislator to new reforms of the Code of Criminal Procedure of the Russian Federation. Some of the programmatic political statements of the country's top leadership noted in the work contributes this process. The analysis of the scientific problem under study is carried out taking into account the existing norms of international law, as well as on the basis of the formed historical experience of the domestic procedure for regulating the rules of investigation and trial in criminal cases. The study focuses on the application of such measures of property impact on a person as bail, custody, seizure of property and others. The conclusions are made taking into account statistical indicators and the results of a survey of practical employees of the investigative departments of various departments and the lawyer corps.